Facing Differences: Ethics and Boundaries in Disagreement - Amatullah, Asda; Maghfiroh, Zakiyah Laili; Apriantoro, Muhamad Subhi (Global Research Network, 2024)
Adhering to the Qur’an and the Sunnah is an obligation for every Muslim without exception. Ikhtilaf refers to the divergence between two parties in their quest for truth. Differences, pros and cons, will always arise in the dynamics of life. Disagreements among Muslims can be something beautiful. Differences of opinion, within the framework of knowledge, are considered a blessing; they enrich knowledge and understanding. Many issues faced by the Muslim community already have their foundations and references in the form of evidence from the Qur'an and Hadith. Proper etiquette in responding to differences includes adhering to a balanced methodology, avoiding extremism in religion, refraining from fanaticism toward individuals or groups, maintaining good assumptions about others, and avoiding quarrels and debates.